Effectiveness Of Student Team Achievement Division Cooperative Learning And Direct Instruction In Teaching Reading Comprehension To Students With Different Learning Motivation - Oktaviana, Tyas; Fitriati, Sri Wuli (Universitas Negeri Semarang, 2017)
This study aimed at investigating the effects of Student Team Achievement Division Cooperative Learning (STAD CL) and Direct Instruction (DI) on improving students' reading comprehension with high or low learning motivation at eleventh grade students of Senior High School 1 Kudus and finding solutions and strategies to make teachers have the preference to use of STAD CL and DI in delivering the subject matter while teaching. This study was experimental research named two-way (two-by-two) factorial design. The population of this study was the eleventh year students of State Islamic Senior High School 1 Kudus in the Academic Year 2015/2016. There were five classes from XI-A to XI -E. Each class had 35 students, therefore, the total population was 175 students. Meanwhile the samples of this study were eighty students from four classes selected based on the historical factors and pre-existing ability. 80 students were chosen to be a sample, 40 as STAD CL group and 40 as DI group. Both groups were given the pre-test to measure students' reading skill and after several times of treatments, both groups were given the post-test. The results of this study showed that STAD CL as teaching strategy for teaching reading to those who had high and low learning motivation compared to DI was more effective than DI because most students stated that STAD CL contributed to increase the reading performance in the classroom. Further study may also be conducted to determine whether teachers’ use of STAD CL or DI appears to reduce student anxiety and stress in the classroom to improve students’ reading or even other skills, retention, and student-teacher relationships.